Information Dispute Mediation Communication Model (Case Study of Information Dispute Mediation by the Information Commission of South Kalimantan Province) - Muhari; Kholil; Jamalullail; Dewi Widowati (Jurnal Multidisiplin Madani, 2023)
The existence of the Information Commission as mandated by Law Number 14 of 2008 concerning Public Information Disclosure provides an opportunity for the entire community to be able to access public information from public agencies/institutions. Unfortunately, there are still many parties who have not understand regarding the disclosure of this information so that information disputes arise. It is in this context that the Information Commission plays a role in bridging the resolution of the information conflict, either through mediation or non-litigation adjudication. This study raises the case of mediation of information disputes handled by the South Kalimantan Provincial Information Commission in the 2014-2018 period. This research seeks to answer how the communication model applied by the Information Commission of South Kalimantan Province and how the strategy was carried out in the mediation session. For this reason, this study uses the theory of relationship communication or personal communication, mediation, with qualitative methods and then uses an interpretive paradigm. As for data collection techniques through observation and interviews with informants. The results show that the model used by the South Kalimantan Provincial Information Commission is: 1) Psychological and Cultural Communication; 2) Two Way Communication and Separate Communication; and 3) Communication of Information is Human Rights